(untitled) (Politeja, 2021)
The paper discusses one of the most important debates on the meaning of constitutional adjudication in the 20th century that engaged two eminent legal and political thinkers Hans Kelsen and Carl Schmitt. The paper focuses on the constitutional dispute over the guardianship of the constitution in the final years of Weimar’s Germany and reconstructs the arguments of the two major protagonists in this dispute concerning the Weimar constitution and the fundamental question whether the guardian of the constitution is (or should be) the constitutional court or the president of the Reich. The debate highlights the complexity of the political problems of a democratic state, as well as the intricate relationship between law and state and has retained high level of topicality. The paper also pays attention to the philosophical-political premises that underlined the distinctly different views on the relationship between law and politics in the thought of Hans Kelsen and Carl Schmitt.